Investing in on-farm and post-harvest resilience to climate change in smallholder value chains: Lessons from Rwanda - Rugege, Denis; Vermeulen, Sonja J. (2017)
This study assessed intermediate results of an investment intended to support climate change adaptation and resilience-building among farmers’ cooperatives in Rwanda. The assessment was based on a purposive sampling survey of farmers’ perspectives conducted in sites in 10 programme intervention districts of the country’s 30 districts. Assessed interventions included the enhancing of farmer-access, quality and utilization of climate information services; onfarm participatory trials of climate-smart crop and forage varieties; and climate-smart harvest and post-harvest support for infrastructural development at “HUBs” for shared post-harvest storage and marketing. Interventions included the capacity development among farmers’ organizations to access funding from commercial lending for integrating climate-smart features in warehouse construction and in other post-harvest infrastructure. Demonstration infrastructures were also constructed by a funding arrangement between the programme, local government structures and farmers’ organizations.